Artifacts of Glory and Pain: Evolving Cultural Narratives on Confederate Symbolism and Commemoration in a New Era of Social Justice - John H. Jameson (Humanities)
The American Civil War has been commemorated with a great variety of monuments, memorials, and markers. These monuments were erected for a variety of reasons, beginning with memorialization of the fallen and later to honor aging veterans, commemoration of significant anniversaries associated with the conflict, memorialization of sites of conflict, and celebration of the actions of military leaders. Sources reveal that during both the Jim Crow and Civil Rights eras, many monuments were erected as part of an organized propaganda campaign to terrorize African American communities and distort the past by promoting a “Lost Cause” narrative. Through subsequent decades, to this day, complex and emotional narratives have surrounded interpretive legacies of the Civil War. Instruments of commemoration, through both physical and digital intervention approaches, can be provocative and instructive, as the country deals with a slavery legacy and the commemorated objects and spaces surrounding Confederate inheritances. Today, all of these potential factors and outcomes, with internationally relevance, are surrounded by swirls of social and political contention and controversy, including the remembering/forgetting dichotomies of cultural heritage. In this article, drawing from the testimony of scholars and artists, I address the conceptual landscape of approaches to the presentation and evolving participatory narratives of Confederate monuments that range from absolute expungement and removal to more restrained ideas such as in situ re-contextualization, removal to museums, and preservation-in-place. I stress not so much the academic debate but how the American public is informed about and reacts to the various issues related to Confederate memorialization. My main point, where my premise stands out in the literature, is that, for the sake of posterity, and our ability to connect and engage with a tangible in situ artifact, not all Confederate statues should be taken down. Some of them, or remnants of them, should be preserved as sites of conscience and reflection, with their social and political meanings ongoing and yet to be determined in the future. The modern dilemma turns on the question: In today’s new era of social justice, are these monuments primarily symbols of oppression, or can we see them, in select cases, alternatively as sites of conscience and reflection encompassing more inclusive conversations about commemoration? What we conserve and assign as the ultimate public value of these monuments rests with how we answer this question.